Victorian Supreme Court Perjury sample 1855-1914 - Finnane, Mark (ADA Dataverse, 2024)
This is a sample of Perjury charges heard at the Victorian Supreme Court between 1855-1914. It was generated to support a study reported in an article published in History Australia 2024 (in press). The 277 cases make up about 20% of the total prosecutions for perjury in the court during this period and recorded in the Prosecution Project database, available to public search at https://app.prosecutionproject.griffith.edu.au/web/public-search.